Evaluation of the influence of building façade design on the acoustic characteristics and auditory perception of urban spaces. Issue 1 (March 2018) - Calleri, Cristina; Shtrepi, Louena; Armando, Alessandro; Astolfi, Arianna
Auditory perception has been proved to have an influence on how we live and move through places and on the use of public spaces. However, despite the numerous studies that have focused on the theme of soundscape and auditory perception of urban spaces, these aspects have not been studied in connection with the design of the building surrounding such spaces. This study focuses on the influence of façade design on acoustic characteristics of an urban space and on the subjective spatial perception of the users. Simulations and auralizations have been conducted through ODEON software (v.13) on the virtual model of a small square of Turin (Italy). Different absorption and scattering coefficients of façade upholsteries have been applied to the façades of the building surrounding the square, choosing from a pool of typical building façade materials. Results of a listening test have proved that the absorption coefficient of the façades has an influence on the subjective perception of space wideness. Moreover, multiple regression analysis has been conducted in order to find a mathematical relation between space wideness perception and objective acoustic parameters. It was shown that the relation between the perceptual aspects and the objective parameters is strongly dependent on the listening position.